Peran Malassezia spp. pada Dermatitis Seboroik: Literature Review - Vinolia Sandhyano Alkautsar Putri Walyatalattof; Hapsari Triandriyani; Hadi Firmansyah S (Lembaga Pengembangan Kinerja Dosen, 2026)
orrheic dermatitis (DS) is a chronic inflammatory skin disease that is commonly found in areas of the body rich in sebaceous glands, such as the scalp, central face, and upper chest. The disease is characterized by lesions that can be reddish plaques with oily scales, as well as itchy complaints. The etiology of DS is multifactorial, where in addition to genetic factors, environmental factors, and immunology also play an important role. One of the main factors in the pathogenesis of DS is infection by Malassezia spp., specifically M. globosa and M. restricta, which play a role in triggering an inflammatory response. This fungus, which is a normal flora on human skin, can transform into opportunistic pathogens under certain conditions, such as microbiota dysbiosis, increased sebum production, or disorders in the skin barrier. Malassezia's metabolic activities, such as oleic acid production, can impair the integrity of the epidermis and lead to the hyperproliferation of keratinocytes. In addition, activation of pattern-recognition receptors in immune cells triggers the inflammatory pathway IL-23/IL-17, which worsens inflammatory conditions in the skin. A deep understanding of the role of Malassezia spp. in the pathogenesis of DS is essential for determining accurate diagnosis and the development of more effective management, including the use of targeted antifungal therapies.